A brominated flame-retardant PC / PBT alloy composition resistant to light aging and its preparation method and application
By using brominated PC with a specific starting decomposition temperature and controlling component mass ratio in brominated flame retardant PC/PBT alloy materials, the island-shaped morphological structure is formed, which solves the problem of material impact intensity and flame retardant performance degradation after photoaging, and realizes the photo-aging performance of the material in outdoor applications.
Patent Information
- Application Number
- CN202211596178.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-13
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-12-13
AI Technical Summary
The impact strength of the existing bromine flame-retardant PC/PBT alloy materials is not high, and the flame retardant performance and impact strength are significantly reduced after photoaging, limiting its outdoor applications.
By using brominated PCs with a specific starting decomposition temperature and controlling the mass ratio of PCs and brominated PCs to PBT in the range of 0.2 to 0.7, a uniform and stable island-shaped morphological structure is formed, which improves the initial impact strength and flame retardant properties of the material, and maintains good performance after photoaging.
The bromine flame-retardant PC/PBT alloy material still maintains good flame retardant performance and impact strength after photoaging, solving the problem of the degradation of existing materials after photoaging.
Smart Images

Figure SMS_1 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The present invention relates to the field of engineering plastics, and more specifically, to a light aging resistant bromine-based flame retardant PC / PBT alloy composition, a preparation method and application thereof. Background Art
[0002] Brominated flame-retardant polycarbonate / polybutylene terephthalate (PC / PBT) alloy is a high-performance alloy material with the advantages of low internal stress, high toughness, high surface gloss, and good processing fluidity. At the same time, the addition of polybutylene terephthalate can significantly improve the chemical resistance of the alloy material and further expand its application areas. It is widely used in electronic appliances, kitchen and bathroom, audio-visual equipment, low-speed travel and other fields.
[0003] In the prior art, the brominated flame retardants commonly used in brominated flame retardant PC / PBT alloys include brominated polycarbon, brominated epoxy and brominated polystyrene, such as the Chinese patent entitled "Halogen-free sulfonate and / or sulfinate used as flame retardant, flame retardant synergist and free radical generator in plastics", which can bring good flame retardant effect. However, the amount of brominated flame retardant required in brominated flame retardant PC / PBT alloy is relatively high, which greatly affects the mechanical properties of the alloy material, especially the impact strength; in addition, the above-mentioned brominated flame retardant is easily degraded during the light aging process, which will not only significantly reduce the flame retardant properties of the alloy material after light aging, but also significantly reduce the impact strength of the alloy material after light aging, which makes the brominated flame retardant PC / PBT alloy subject to obvious restrictions in outdoor application environments.
[0004] Therefore, it is necessary to solve the problem that the impact strength of existing brominated flame-retardant PC / PBT alloys is not high, and the flame retardant properties and impact strength decrease significantly after light aging. Summary of the invention
[0005] The primary purpose of the present invention is to overcome the problem that the impact strength of the existing bromine-based flame-retardant PC / PBT alloy is not high, and the flame retardant performance and impact strength are significantly reduced after light aging, and to provide a bromine-based flame-retardant PC / PBT alloy composition resistant to light aging. The bromine-based flame-retardant PC / PBT alloy composition has good flame retardant performance and impact strength, and after light aging, it can still maintain good flame retardant performance and impact strength.
[0006] A further object of the present invention is to provide a method for preparing the above-mentioned brominated flame-retardant PC / PBT alloy composition.
[0007] A further object of the present invention is to provide an application of the above-mentioned brominated flame-retardant PC / PBT alloy composition in the preparation of low-speed travel equipment products.
[0008] The above-mentioned object of the present invention is achieved by the following technical solutions:
[0009] A brominated flame-retardant PC / PBT alloy composition resistant to light aging comprises the following components in parts by weight:
[0010]
[0011] The brominated PC is a copolymer of phosgene, tetrabromobisphenol A and bisphenol A; the initial decomposition temperature of the brominated PC is ≥460°C; the ratio of the sum of the mass of the PC and the brominated PC to the mass of PBT is 1:(0.2-0.7).
[0012] It should be understood that the initial decomposition temperature of the present invention refers to: the temperature at which the mass loss of the test object (such as brominated PC) is 5% recorded by a thermal gravimetric analyzer (TGA) at a heating rate of 20°C / min from room temperature to 750°C under a nitrogen atmosphere, which is the initial decomposition temperature.
[0013] The inventor of the present invention unexpectedly discovered that by adding brominated PC with a specific initial decomposition temperature and controlling the mass ratio of PC and brominated PC to PBT within a specific range, the brominated flame-retardant PC / PBT alloy composition can have good flame retardant properties and impact strength, and its flame retardant properties and impact strength after light aging remain good. The reason is that when the mass ratio of PC and brominated PC to PBT is controlled within a specific range, the material can form a uniform and stable island-like morphology structure with PC and brominated PC as continuous phases and PBT as island phases. On the one hand, this island-like morphology structure can make the initial impact strength of the material reach a high level; on the other hand, the island-like morphology structure ensures that the phase state and phase interface of the material are stable during the light aging process, and the brominated PC will not significantly degrade and produce small molecular substances during the light aging process. Through the synergistic effect of the island-like morphology structure and the brominated PC with a specific initial decomposition temperature, the brominated flame-retardant PC / PBT alloy composition obtained can still maintain good flame retardant properties and impact strength after light aging.
[0014] That is, the bromine-based flame-retardant PC / PBT alloy composition of the present invention has good flame retardancy and impact strength, and after light aging, it can still maintain good flame retardancy and impact strength.
[0015] Preferably, the brominated flame retardant PC / PBT alloy composition comprises the following components in parts by weight:
[0016]
[0017]
[0018] Preferably, the initial decomposition temperature of the brominated PC is 466-489°C.
[0019] Preferably, the mass fraction of bromine element in the brominated PC is 20-22%.
[0020] The synthesis of the brominated PC of the present invention can refer to the conventional process steps for synthesizing polycarbonate.
[0021] The present invention provides a better method for preparing brominated PC, specifically:
[0022] The preparation method of brominated PC comprises the following steps: mixing bisphenol A, tetrabromobisphenol A, 8-12% sodium hydroxide aqueous solution and sodium bisulfite, stirring at 20-30° C. for 1-2 hours to generate bisphenol A and tetrabromobisphenol A sodium salt; then adding a dichloromethane solution containing 8-12% phosgene and cooling to -3-3° C., continuously stirring to carry out interfacial polycondensation reaction; then standing for 1-2 hours, removing the upper clear liquid, washing the lower turbid liquid with deionized water to neutrality, and then precipitating the product with anhydrous ethanol, filtering and drying to obtain the brominated PC.
[0023] Among them, by adjusting the interfacial polycondensation reaction time and the amount of phosgene concentration, brominated PC with different initial decomposition temperatures can be obtained; by adjusting the dosage ratio of bisphenol A and tetrabromobisphenol A, brominated PC with different bromine element mass fractions can be obtained.
[0024] PC, PBT, toughening agent, ester exchange inhibitor, weathering agent and anti-dripping agent commonly used in the art can be used in the present invention.
[0025] Preferably, the average molecular weight of the PC is 25,000-36,000.
[0026] Preferably, the viscosity of the PBT is 0.85-1 dl / g.
[0027] Preferably, the toughening agent is an acrylic-silicone rubber toughening agent.
[0028] Preferably, the transesterification inhibitor is sodium dihydrogen phosphate.
[0029] Optionally, the weathering agent is at least one of 2-(2'-hydroxy-3',5'bis(a,a-dimethylbenzyl)phenyl)benzotriazole or 2-[2-hydroxy-4-[3-(2-ethylhexyloxy)-2-hydroxypropoxy]phenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine.
[0030] Optionally, the anti-dripping agent is SAN-coated PTFE or pure PTFE powder.
[0031] Preferably, the bromide-based flame-retardant PC / PBT alloy composition further comprises 0.01 to 2 parts of a processing aid.
[0032] More preferably, the processing aid is an antioxidant or a lubricant.
[0033] Optionally, the antioxidant is at least one of tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane, tris(2,4-di-tert-butylphenyl) phosphite or distearylthiopropionate.
[0034] Optionally, the lubricant is at least one of pentaerythritol stearate, polyethylene wax or silicone lubricant.
[0035] The preparation method of the bromine-based flame-retardant PC / PBT alloy composition comprises the following steps: mixing, melting, extruding and granulating the components to obtain the bromine-based flame-retardant PC / PBT alloy composition.
[0036] Preferably, the preparation method comprises the following steps: stirring and mixing the components, then melting, extruding and granulating in a twin-screw extruder to obtain the bromide-based flame-retardant PC / PBT alloy composition.
[0037] More preferably, the aspect ratio of the twin-screw extruder is 40-45:1, the barrel temperature is 210-260° C., and the screw speed is 500-600 rpm.
[0038] The application of the above-mentioned brominated flame-retardant PC / PBT alloy composition in the preparation of low-speed travel equipment products is also within the protection scope of the present invention.
[0039] Preferably, the low-speed travel equipment product is a charging pile or a shared bicycle lock.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] The bromine-based flame-retardant PC / PBT alloy composition of the present invention has good flame-retardant properties and impact strength, and can still maintain good flame-retardant properties and impact strength after light aging. DETAILED DESCRIPTION
[0042] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.
[0043] Some of the reagents selected in the embodiments and comparative examples of the present invention are described as follows:
[0044] PC1#: 1300 10NP, LG Chemical Co., Ltd., South Korea, average molecular weight 25000;
[0045] PC2#: 7030PJ, Mitsubishi Group, Japan, average molecular weight 36000;
[0046] PC3#: 7025PJ, Mitsubishi Group, Japan, average molecular weight 28000;
[0047] PC4#: 1300 22NP, LG Chemical Co., Ltd., South Korea, average molecular weight 20,000;
[0048] PBT1#: GX112, Sinopec Yizheng Chemical Fiber Co., Ltd., viscosity 0.85 mL / g;
[0049] PBT2#: GX121, Sinopec Yizheng Chemical Fiber Co., Ltd., viscosity 0.98mL / g
[0050] PBT3#: 1100-211M, Changchun Man-Made Resin Co., Ltd., Taiwan, China, viscosity 1.0 dl / g;
[0051] PBT4#: GL236, Sinopec Yizheng Chemical Fiber Co., Ltd., viscosity 1.3dl / g;
[0052] Toughener 1#: acrylic-silicone rubber toughener, S-2130, Mitsubishi, Japan;
[0053] Toughener 2#: methyl methacrylate-butadiene-styrene copolymer, M-521, made by Kanebuchi, Japan;
[0054] Ester exchange inhibitor 1#: sodium dihydrogen phosphate, MSP2040, Shengdu Chemical;
[0055] Transesterification inhibitor 2#: zinc dihydrogen phosphate, BUDIT T21, Budenheim, Germany;
[0056] Weathering agent: 2-(2'-hydroxy-3',5'bis(a,a-dimethylbenzyl)phenyl)benzotriazole, commercially available;
[0057] Anti-drip agent: polytetrafluoroethylene, commercially available;
[0058] Processing aids: antioxidant, tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane, commercially available;
[0059] Antimony white: commercially available.
[0060] Bromide PC1#: Homemade, the preparation method is as follows: add 300g bisphenol A, 100g tetrabromobisphenol A, 1800g 10% sodium hydroxide aqueous solution and 1g sodium bisulfite into a reactor and stir at 25°C for 1 hour to generate bisphenol A sodium salt and tetrabromobisphenol A sodium salt; then add 5000g dichloromethane solution containing 10% phosgene and cool to 0°C, and continue stirring for 1.5 hours for interfacial polycondensation reaction. Let the reactor stand for 1 hour, pour out the upper clear liquid, wash the lower turbid liquid with deionized water until neutral, then use 10Kg of anhydrous ethanol to precipitate the product, filter it and put it into an oven to dry at 100°C for 12 hours to obtain bromide PC1#. The initial decomposition temperature of bromide PC1# is 466°C, and the bromine content is 22% determined by X-ray fluorescence spectrometry.
[0061] Bromide PC2#: Homemade, the preparation method is basically the same as that of bromide PC1#, except that: 5600g of dichloromethane solution containing 10% phosgene was added; the interfacial polycondensation reaction was carried out by continuous stirring for 1.85h. Finally, bromide PC2# was obtained. The initial decomposition temperature of bromide PC2# was 489℃, and the bromine content was 21% as determined by X-ray fluorescence spectrometry.
[0062] Bromide PC3#: Homemade, the preparation method is basically the same as that of bromide PC1#, except that: 4700g of dichloromethane solution containing 10% phosgene was added; the interfacial polycondensation reaction was carried out by continuous stirring for 1.28h. Finally, bromide PC3# was obtained. The initial decomposition temperature of bromide PC3# is 460℃, and the bromine content is 22%.
[0063] Brominated PC4#: Homemade, the preparation method is basically the same as that of brominated PC1#, except that 335g of bisphenol A and 100g of tetrabromobisphenol A are used. The initial decomposition temperature of brominated PC4# is 466°C, and the bromine content is 20% as determined by X-ray fluorescence spectrometry.
[0064] Brominated PC5#: Homemade, the preparation method is basically the same as that of brominated PC1#, except that 420g of bisphenol A and 100g of tetrabromobisphenol A are used. The initial decomposition temperature of brominated PC5# is 466℃, and the bromine content is 15% as determined by X-ray fluorescence spectrometry.
[0065] Bromide PC6#: Homemade, the preparation method is basically the same as that of bromide PC1#, except that: 4500g of dichloromethane solution containing 10% phosgene is added; the interfacial polycondensation reaction is carried out by continuous stirring for 1h. Finally, bromide PC6# is obtained. The initial decomposition temperature of bromide PC6# is 392℃, and the bromine content is 22% determined by X-ray fluorescence spectrometry.
[0066] Brominated PC7#: Homemade, the preparation method is basically the same as that of brominated PC1#, except that bisphenol A is not added; the interfacial polycondensation reaction is carried out under continuous stirring for 1.5 hours. Finally, brominated PC7# is obtained, the initial decomposition temperature of brominated PC7# is 460℃, and the bromine content is 58% as determined by X-ray fluorescence spectrometry.
[0067] Brominated polycarbon: FG8500, initial decomposition temperature 446°C, Teijin;
[0068] Brominated epoxy: F-2100, initial decomposition temperature 364°C, Israel Chemicals;
[0069] Brominated polyphenylene: SAYTEX 621, initial decomposition temperature 379°C, Albemarle, USA.
[0070] Unless otherwise specified, the components (such as weathering agents, anti-dripping agents, and other additives) selected in the parallel examples and comparative examples are all the same commercially available products.
[0071] The performance of the brominated flame retardant PC / PBT alloy compositions provided in the embodiments and comparative examples of the present invention was measured according to the following test method:
[0072] Impact strength: The impact strength of the test specimens was tested according to the ASTM D256-2010 standard. In addition, an aging test was performed according to the ISO4892.2:2013 standard. The specimens were placed in a xenon lamp aging box for xenon lamp aging. After 1000 hours, the specimens were taken out for impact strength testing and the results were recorded. The performance retention rate of the impact strength before and after aging was compared as a measure of the light aging stability. The higher the performance retention rate, the better the xenon lamp aging stability.
[0073] Flame retardant performance: The flammability test was conducted according to the standard of "Flammability Test of Plastic Materials, UL94-2019". In addition, the sample was placed in a xenon lamp aging box for xenon lamp aging. After 1000 hours, the sample was taken out for flammability test and the results were recorded. The flame retardant grade is derived based on the burning rate, extinguishing time, ability to resist dripping, and whether the dripping is burning. The sample used for the test: 125mm length and 13mm width. The thickness of the present invention was selected as 1.0mm during the test. According to the UL94-2019 standard, the flame retardant grade of the material can be classified as UL94 V0, V1, V2, etc.
[0074] The preparation process of the bromine-based flame-retardant PC / PBT alloy composition of each embodiment of the present invention and the comparative example is as follows: the components are mixed uniformly according to the formula to obtain a premix; the premix is put into a twin-screw extruder, melt-mixed and extruded into granules in the twin-screw extruder (the screw aspect ratio is 45:1, the barrel temperature is 250°C, and the screw speed is 500rpm) to obtain a bromine-based flame-retardant PC / PBT alloy composition.
[0075] Examples 1 to 20
[0076] Examples 1 to 20 provide a series of brominated flame retardant PC / PBT alloy compositions, the formulations of which are shown in Tables 1 and 2.
[0077] Table 1 Formulas of Examples 1 to 8 (parts by weight)
[0078]
[0079] Table 2 Formulas of Examples 9 to 20 (parts by weight)
[0080]
[0081]
[0082] Comparative Example 1
[0083] This comparative example provides a brominated flame-retardant PC / PBT alloy composition, the formula of which is different from that of Example 1 in that brominated PC1# is replaced by brominated PC6#.
[0084] Comparative Example 2
[0085] This comparative example provides a brominated flame retardant PC / PBT alloy composition, the formula of which is different from that of Example 1 in that brominated PC1# is replaced by brominated PC7#.
[0086] Comparative Example 3
[0087] This comparative example provides a PC / PBT alloy composition, the formula of which is different from that of Example 1 in that no brominated PC1# is added.
[0088] Comparative Example 4
[0089] This comparative example provides a brominated flame retardant PC / PBT alloy composition, the formula of which is different from that of Example 1 in that brominated PC1# is replaced by brominated polycarbohydrate.
[0090] Comparative Example 5
[0091] This comparative example provides a brominated flame-retardant PC / PBT alloy composition, the formula of which is different from that of Example 1 in that brominated PC1# is replaced by brominated epoxy.
[0092] Comparative Example 6
[0093] This comparative example provides a brominated flame-retardant PC / PBT alloy composition, the formula of which is different from that of Example 1 in that brominated PC1# is replaced by brominated polyphenylene.
[0094] Comparative Example 7
[0095] This comparative example provides a brominated flame-retardant PC / PBT alloy composition, the formula of which is different from that of Example 6 in that the amount of PBT1# used is 14 parts, and by calculation, the mass ratio of (PC+brominated PC):PBT is 1:0.15.
[0096] Comparative Example 8
[0097] This comparative example provides a brominated flame-retardant PC / PBT alloy composition, the formula of which is different from that of Example 7 in that the amount of PBT1# used is 40 parts, and by calculation, the mass ratio of (PC+brominated PC):PBT is 1:0.8.
[0098] The properties of the brominated flame retardant PC / PBT alloy composition / PC / PBT alloy composition of each embodiment and comparative example were measured according to the above-mentioned test method. The test results are shown in Table 3.
[0099] Table 3 Performance test results of various embodiments and comparative examples
[0100]
[0101]
[0102] From Table 3, we can see that:
[0103] The initial flame retardant properties of the bromine-based flame-retardant PC / PBT alloy compositions of Examples 1 to 20 are all V-0 level, the initial impact strength is above 669 J / m, the flame retardant properties remain at the V-0 level after xenon lamp aging, and the retention rate of the impact strength after xenon lamp aging is above 72%, indicating that the bromine-based flame retardant PC / PBT alloy composition of the present invention has good flame retardant properties and impact strength, and after light aging, it can still maintain good flame retardant properties and impact strength.
[0104] It can be seen from Examples 1 to 5 that by adjusting the amount of each component within a suitable range (Examples 1, 4, and 5), the retention rate of the impact strength of the brominated flame-retardant PC / PBT alloy composition after xenon lamp aging is above 83%.
[0105] From Examples 1, 9 to 11, it can be seen that by selecting polycarbonate with a suitable average molecular weight (25,000 to 36,000), the initial impact strength of the brominated flame-retardant PC / PBT alloy composition obtained is above 702 J / m, and the retention rate of the impact strength after xenon lamp aging is above 78%.
[0106] From Examples 1, 12 to 13, it can be seen that by selecting brominated PC with an initial decomposition temperature within a specific range (466 to 489° C.), the brominated flame-retardant PC / PBT alloy composition obtained has a higher initial impact strength (above 703 J / m) and a higher retention rate of impact strength after xenon lamp aging (above 83%).
[0107] It can be seen from Examples 1 and 14 to 15 that by selecting brominated PC with a bromine mass fraction within a specific range (20 to 22%), the brominated flame retardant PC / PBT alloy composition obtained has a higher initial impact strength (above 701 J / m) and a higher retention rate of impact strength after xenon lamp aging (above 81%).
[0108] It can be seen from Examples 1 and 16 to 18 that by selecting PBT with a suitable viscosity (0.85 to 1.0 dl / g), the brominated flame-retardant PC / PBT alloy composition obtained has a higher initial impact strength (above 697 J / m) and a higher retention rate of impact strength after xenon lamp aging (above 82%).
[0109] It can be seen from Examples 1, 19 and 20 that by selecting the specific toughening agent (Example 1) or the specific ester exchange inhibitor (Example 1), the brominated flame retardant PC / PBT alloy composition obtained has a higher initial impact strength and a higher retention rate of impact strength after xenon lamp aging.
[0110] In comparative example 1, brominated PC6# was added, whose initial decomposition temperature was too low, and the retention rate of the impact strength of the obtained brominated flame retardant PC / PBT alloy composition after xenon lamp aging was only 23%, and the impact strength decreased significantly. In comparative example 2, brominated PC7# was added. During the preparation of brominated PC7#, only tetrabromobisphenol A was added, and bisphenol A was not added. The impact strength of the obtained brominated flame retardant PC / PBT alloy composition after xenon lamp aging still decreased significantly. In Comparative Example 3, no brominated PC is added, and the initial flame retardant properties of the brominated flame retardant PC / PBT alloy composition obtained are poor, and the impact strength after xenon lamp aging also decreases significantly; in Comparative Examples 4 to 6, brominated polycarbonate, brominated epoxy and brominated polyphenylene are added respectively, and the impact strength of the brominated flame retardant PC / PBT alloy compositions obtained after xenon lamp aging decreases significantly, and the flame retardant properties of Comparative Examples 5 and 6 after xenon lamp aging also deteriorate; in Comparative Examples 7 and 8, the ratio of the sum of the mass of PC and brominated PC to the mass of PBT is not properly controlled, and the impact strength of the brominated flame retardant PC / PBT alloy compositions obtained after xenon lamp aging decreases significantly.
[0111] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A brominated flame-retardant PC / PBT alloy composition resistant to light aging, characterized in that: The composition comprises the following components in parts by weight: PC30~65 parts, Brominated PC 15~30 parts, PBT18~40 parts, 3~10 parts of toughening agent, Antimony white 0.5~5 parts, 0.1-0.8 parts of transesterification inhibitor, Weathering agent 0.1~1 part, Anti-dripping agent 0.2~2 parts; The brominated PC is a copolymer of phosgene, tetrabromobisphenol A and bisphenol A; the initial decomposition temperature of the brominated PC is ≥460°C; the ratio of the sum of the mass of the PC and the brominated PC to the mass of PBT is 1:(0.2~0.7); The initial decomposition temperature refers to the temperature at which the mass weight loss of brominated PC is 5% when the temperature is increased from room temperature to 750° C. at a heating rate of 20° C. / min under a nitrogen atmosphere using a thermogravimetric analysis tester. This is the initial decomposition temperature.
2. The brominated flame retardant PC / PBT alloy composition according to claim 1, characterized in that: The initial decomposition temperature of the brominated PC is 466-489°C.
3. The brominated flame retardant PC / PBT alloy composition according to claim 1, characterized in that: The mass fraction of bromine element in the brominated PC is 20-22%.
4. The brominated flame retardant PC / PBT alloy composition according to claim 1, characterized in that: The average molecular weight of the PC is 25000-36000.
5. The brominated flame retardant PC / PBT alloy composition according to claim 1, characterized in that: The viscosity of the PBT is 0.85-1.0 dl / g.
6. The brominated flame retardant PC / PBT alloy composition according to claim 1, characterized in that: The toughening agent is an acrylic-silicone rubber toughening agent.
7. The brominated flame retardant PC / PBT alloy composition according to claim 1, characterized in that: The transesterification inhibitor is sodium dihydrogen phosphate.
8. The brominated flame retardant PC / PBT alloy composition according to claim 1, characterized in that: The bromide-based flame-retardant PC / PBT alloy composition further comprises 0.01 to 2 parts of a processing aid.
9. The method for preparing the brominated flame-retardant PC / PBT alloy composition according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing, melting, extruding and granulating the components to obtain the bromine-based flame-retardant PC / PBT alloy composition.
10. Use of the brominated flame-retardant PC / PBT alloy composition according to any one of claims 1 to 8 in the preparation of low-speed travel equipment products.
Citation Information
Patent Citations
High temperature and high humidity resistant polycarbonate composition and preparation method thereof
CN109021534A
Flame-retardant ABS composite material as well as preparation method and application thereof
CN113912975A